Arabic Teaching and Learning on Construction of Modern Instruction in Muslim Minority Pesantren Society - Ismail Suardi Wekke (Edukasia Islamika : Jurnal Pendidikan Islam, 2018)
This present study explores the practices of teaching and learning Arabic among Muslim minorities by using the approach of modernity principles. A qualitative descriptive approach was designed in this research. It was conducted in West Papua, which covered five regencies and one city. The findings demonstrate that the instruction served in a number of pesantren (Islamic boarding schools) in Mayamuk, Aimas, Waisai, Teminabuan, Kaimana, Waigom, and Misol was carried out in a structured manner. In these seven locations, Islamic education that adopted a language skill-based instructional framework was presented by applying a communicative approach among santri(pesantren students). The language component fostered among santri was Arabic expressions without any special emphasis on the mastery of grammar. The pesantren atmosphere equipped with a boarding school for santri as a place to stay facilitated interactions among them as well as the instructors to practice their language skills. The skills were situated in the learning context and the accompanying environment. The existing social aspects were then used to mediate the teaching and learning process. The study also reveals that the variety of learning objectives determining the aspects of the approach and methodology affects Arabic instruction in the pesantren settings. It implies that not only does pesantren internalize a religious spirit, but it also promotes Indonesiabased on the spirit of nationalism.